INFLUENCE OF NATIVE LIPOSOMES AND “MEMBRANOSTABIL” PREPARATION ON THE CONTENT OF SOME BLOOD SERUM PROTEIN FRACTIONS IN NEWBORN CALVES - Holopura, S. I.; Tsvilikhovsky, M. I. (Scientific Progress & Innovations, 2020)
The results of applying “Membranostabil” developed by the authors and native liposomes from phospholipid bilayer on the soy lecithin base for the correction of albumins and haptoglobin content value indices in the blood serum of newborn calves during the period of colostral immunity formation have been presented. Albumins and haptoglobin content values in the blood serum of newborn calves have been studied in dynamics – from the 1st day after birth to the 11 days of age. The investigation was carried out in 3 groups of newborn calves of Ukrainian local dairy breed – the control and two experimental. The level of serum protein fractions was investigated by the method of polyacrylamide gel electrophoresis. The quantitative assessment of protein fractions was carried out by electrophoregram scanning with their subsequent graphic reconstruction and by relative units or area calculation using computer program. It was established, that “Membranostabil” and native liposomes from phospholipid bilayer on the soy lecithin base activated the transportation of albumins and haptoglobin in the small intestine and led to reliable growth of their content in comparison with calves in the control group. The dynamics with comparative analysis of albumin and haptoglobin content values in the blood serum between the indices in calves from separate groups was shown. More pronounced growth of albumins and haptoglobin content under the influence of the used native liposomes in the blood of newborn calves was demonstrated. More pronounced effect of “Membranostabil” preparation on the own albumin synthesis by liver cells was found. The preventive effect of native liposomes and “Membranostabil” preparation on developing pathological changes in the experimental calves’ organism was found. It was established that during the period from the first to the third day of calves’ life in every group, the level of haptoglobin in their blood serum dropped drastically with the following increase on the seventh day. Several hypotheses concerning probable reasons of haptoglobin level decreasing in the blood serum of newborn calves on the third day of life were expressed. Lower haptoglobin content (as a protein of an acute phase with immune modulating properties) was found in the blood serum of calves in experimental groups on the 11th day of life in comparison with animals in the control group, which ensures the prevention of the second phase of early immune deficiency, sepsis, the development of digestion disorders and other young animal diseases.